Pathological study of spinal cord atrophy in multiple sclerosis suggests limited role of local lesions - Evangelou, N; DeLuca, G; Owens, T; Esiri, M (2005)
Imaging studies in multiple sclerosis have shown that spinal cord atrophy correlates with clinical disability. The pathological substrate of atrophy has not as yet been investigated adequately. In order to determine the cause of spinal cord atrophy in multiple sclerosis, five different sections of the spinal cord were examined histopathologically in 33 controls and 55 multiple sclerosis cases. In the multiple sclerosis cases in each section the total lesion load and the cross-sectional area of the cord were measured. Multiple regression models were estimated, controlling for sex, age, duration of the disease and location of the cord sections. The multiple sclerosis cords were found to be significantly smaller than the controls. The duration of the disease played the most important role in determining cord atrophy. The degree of atrophy varied in different parts of the cord. Individual lesions played a minor role in local atrophy. Our findings suggest that axonal degeneration, possibly caused by the cumulative number of lesions in the brain and cord, or an alternative atrophic process, is responsible for spinal cord atrophy in multiple sclerosis, rather than tissue loss within individual lesions.